The Antibacterial Effect of Anchovy (Stolephorus Insularis) Extract Against Enterococcus Faecalis - Ilham Mahendra; Istien Wardani; Linda Rochyani (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2018)
Backgrounds: Enterococcus faecalis is a facultative anaerobic gram-positive bacteria that known to have a role in the infection of the root canal, causing the failure of root canal treatment. The extract from anchovy (Stolephorus insularis) contains fluor has antibacterial properties that can inhibit the growth of gram-positive bacteria and has the potential to be developed as a root canal sterilization agent. Purpose : To determine the antibacterial effect of anchovy (Stolephorus insularis) extract to the Enterococcus faecalis. Methods : This study was an true experimental study with post test only control group design and were tested by diffusion methods, consisted of 5 groups: 2 control groups DMSO 1% as negative control and ChKM as positive control, 3 treatment groups of anchovy (Stolephorus insularis) extract with different concentrations of 18%, 24% and 30% which each group consisted of 5 samples. Antivbacterial effect was examined by measuring the clear zone around the filter paper. Data were analyzed by ANOVA test followed by LSD test. Results : Results of this study proved the presence of antibacterial effects of anchovy (Stolephorus insularis) extract to the Enterococcus faecalis. In this study, the higher concentrations used, the greater the antibacterial effect. Average inhibition zone of each groups: DMSO 1% (6,03 mm), ChKM (14,18 mm), 18%(6,83 mm), 24%(7,03 mm) and 30% (7,16 mm). Conclusion : Anchovy (Stolephorus insularis) extract has antibacterial effect to the Enterococcus faecalis.